PELATIHAN PENGELOLAAN KEUANGAN RUMAH TANGGA BAGI WANITA NELAYAN DI DESA NENAS SIAM KABUPATEN BATU BARA - Azizah Mahary; Irham Huspa Siregar; Asep Gunawan (Jurnal Abdi Insani, 2023)
Family financial management is a fundamental skill that must be owned by every household. The wife has an important role in managing family finances because the wife's job is to be the "finance minister" for her family. Financial problems generally occur when the amount of expenditure is greater than the amount of income, and the amount of income earned is irregular. This PKM activity was carried out on Wednesday-Thursday June 7-8 2023, 09.00 to 12.00 WIB at the Nenas Siam Village Hall, Batu Bara Regency with the target of 18 fishermen's wives or women with the aim that participants could identify sources of income and expenses , can determine between needs and wants, and understand how to control expenses according to the budget that has been compiled so that family needs are met. This PKM activity method is carried out in three stages, namely: 1) planning and preparation stage, 2) activity implementation stage, 3) final evaluation stage with lecture techniques, group discussions, and assignment assignments. As a result of this activity, the participants were very enthusiastic about participating in the training, which was marked by the participants following it until the event was over, the participants were able to prepare a family budget by making simple bookkeeping. Based on the results of the activity evaluation, participants hoped that there would be a follow-up program with a similar theme in order to better understand family planning specifically.